Side-out success and ways that points are obtained in women`s college volleyball - Palao, J. M. (Journal of Sports Analytics, 2018)
The purpose of this study was to assess side-out success and ways that points are obtained in relation to the result of the game in women`s college volleyball. A total of 2,435 rallies from 48 sets of the Missouri Valley Conference (NCAA Division I) were analyzed. The variables studied were: game phase, phase efficacy, reason for the success or error, number of times that the ball went over the net, result of the game, attack tempo, reception efficacy, and type of set. The findings provide reference values to guide the analysis of the volleyball team and understand the way winning teams score and build their side-out in the women`s college population. The results show the importance of side-out phase efficacy as a variable to monitor team performance in competition and the individual actions that correlate most with side-out phase success. The action that best differentiates winning and losing teams was the attack after reception. The results show the contribution of different ways to build the side-out. The actions with greater contribution were the ones that increased the setter`s possibilities to build the offense and accelerate the game, such as through the reception efficacy and the use of the jump set.